Er liebte die Menschen und verachtete die Laster. Norbert von Xanten/Magdeburg und die Prämonstratenser in der mittelalterlichen Saxonia (12. Jahrhundert) - Freund, Stephan (Jahrbuch des Hennebergisch-Fränkischen Geschichtsvereins, 2022)
Keywords: 🇩🇪 germany (general); 👤 norbert of xanten

The life of Saint Norbert: founder of the Order of Prémontré : Vita Norberti B - Antry, Theodore James (The Norbertine Canonesses of the Bethlehem Priory of St. Joseph, 2021)
Keywords: 👤 norbert of xanten

Als de Bliksem. Norberts biografie met glasramen - Janssens, Herman (Als de bliksem. 900 jaar norbertijnen en norbertinessen, 2021)
Keywords: 👤 norbert of xanten

In het spoor van Norbert van Gennep Christus navolgen. Een levensideaal in dienst van God en van de Kerk - Janssens, Herman; Ardura, Bernard (Als de bliksem. 900 jaar norbertijnen en norbertinessen, 2021)
Keywords: 👤 norbert of xanten

Norbert de Gennep, une vie d’errance et de prédication - Pacco, Jean-François (Floreffe. Neuf siècles d’histoire, 2021)
Keywords: 👤 norbert of xanten

Christus folgen - Gott suchen: Norbert von Xanten wurde in eine Welt der religiösen Um- und Aufbrüche hineingeboren - die Lust am niemals abgeschlossenen Lebensexperiment begleitete ihn : in seiner rigorosen Gottessuche war er ein Kind seiner gärenden Zeit - wenn auch ein außergewöhnliches und einzigartiges - Schneidmüller, Bernd (Damals, 2021)
Keywords: 👤 norbert of xanten

The Canons Regular: St Norbert and the Premonstratensians - Thonippara, Francis (Vinayasādhana: Dharmaram Journal of Psycho-Spiritual Formation, 2021)
Keywords: 👤 norbert of xanten; 📚 premonstratensian (general)

Celebrando a Paz e causando Conflitos: as diferentes facetas de Norberto de Xanten - Araujo, Vinicius Cesar Dreger de (Revista Escripturas, 2020)
Norbert of Xanten, founder of the Order of the PremonstratensianRegular Canons (1120) is an exemplary figure both in clerical reforms and in religious effervescence between the 11th and 12th centuries. We will analyze Norbert's performances as a peacemaker in Lotharingia in 1119, as an itinerant preacher and as a cause of conflicts in Magdeburg between 1126 and 1129, already as archbishop in the light of the Spielregln der Politik(by Gerd Althoff) and the Konsensuale Herrschaft(by Bernd Schneidmüller). For this purpose, we will use Vita Norberti Aas ourmain source, complemented when necessary by Vita Norberti B,the Gesta archiepiscoporum magdeburgensiumand the Annales Magdeburgenses.
Keywords: 👤 norbert of xanten

Man on Fire. The Life and Spirit of Norbert of Xanten - Kunkel, Thomas (Center for Norbertine Studies, 2019)
Keywords: 👤 norbert of xanten

San Norberto en algunas estampas flamencas del siglo XVII - Calvo Portela, Juan Isaac (Espacio, Tiempo y Forma. Serie VII, Historia del Arte, 2018)
Keywords: 👤 norbert of xanten

The Translation of St. Norbert’s Remains to Prague in 1627: True account of a letter sent by St. Michael’s of Antwerp to the Canons Regular of the Monastery of Saint Norbert of Madrid - Sands, Rosemary (Communicator: The English Speaking Circary of the Order of Prémontré, 2018)
Keywords: 👤 norbert of xanten

Mönch oder Kanoniker?: Bernhard von Clairvaux versus Norbert von Xanten - Winkler, Gerhard (Patrimonium Cisterciense, 2017)
Keywords: 👤 norbert of xanten

St. Norbert and His Order (Mediatrix Press, 2015)
Keywords: 👤 norbert of xanten; 📚 premonstratensian (general)

Norbert Ksantenskiy i sv. Avgustin. K voprosu ikonografii miniatyury v rukopisi «Vita beati Norberti» iz sobraniya Bavarskoy gosudarstvennoy biblioteki/Норберт Ксантенский и св. Августин. К вопросу иконографии миниатюры в рукописи «Vita beati Norberti» из собрания Баварской государственной библиотеки - Zotova, Yelizaveta Valentinovna (Observatoriya kul'tury, 2014)
The article is devoted to the study of the only surviving illuminated manuscript of the life of Norbert of Xanten. The author analyzes the iconography of the miniature from this manuscript, compares it with miniatures and other illuminated lives of the holy archbishops, manuscripts of the works of St. Augustine, created in Germany in the same period (XII century).
Keywords: 👤 norbert of xanten

A Norbert for England: Holy Trinity and the Invention of Robert of Knaresborough - Easterling, Joshua (Journal of Medieval Monastic Studies, 2013)
This essay considers the relationship between two monastic vitae and their historical subjects. The prose vita of the English hermit Robert of Knaresborough that is extant in London, British Library, MS Egerton 3143 contains a number of passages borrowed from the Vita B of Norbert of Xanten, the founder of Premontre. These two otherwise unaffiliated figures of religious reform are connected through Robert’s biographer, most likely a brother of the late-established Trinitarian Order, who extracted key details from Norbert’s vita to shape Robert in the founder’s image. In Egerton’s prose vita, Robert is ultimately made to serve as a legitimate origin for, and as a founder of, the Trinitarian Order at Knaresborough.
Keywords: 👤 norbert of xanten

Das Leere Grab des heiligen Norbert - Ullrich, Sabine (Magdeburg : Die 99 besonderen Seiten der Stadt Sabine Ullrich, 2013)
Keywords: 👤 norbert of xanten

Der heilige Norbert: Erzbischof und Ordensgründer - Handgrätinger, Thomas (Norbertus-Verlag, 2011)
Keywords: 👤 norbert of xanten

Norbert von Xanten und der Orden der Prämonstratenser: Sammelband zur historischen Vortragsreihe im Norbertjahr 2009-2010 in Magdeburg - Dölken, Clemens (Norbertus-Verl., 2010)
Keywords: 👤 norbert of xanten; 📚 premonstratensian (general)

Norbert von Xanten, die Gründung von Prémontré und die Entstehung des Prämonstratenserordens - Felten, Franz J. (Norbert von Xanten und der Orden der Prämonstratenser : Sammelband zur historischen Vortragsreihe im Norbertjahr 2009/2010 in Magdeburg, 2010)
Keywords: prémontré; 👤 norbert of xanten

Norbert von Xanten: der Gründer des Prämonstratenserordens und seine Zeit - Halder, Klemens H. (Tyrolia-Verl., 2010)
Keywords: 👤 norbert of xanten

"Allen bin ich alles geworden, um auf jeden Fall einige zu retten" (1 Kor 9,22): Norbert von Xanten und die Geschichte des Prämonstratenserordens - Lerchenmüller, Petrus-Ardrian (Windberger Schriftenreihe, 2009)
Keywords: 👤 norbert of xanten; 📚 premonstratensian (general)

Norbert and early Norbertine spirituality - Antry, Theodore J.; Neel, Carol (Classics of Western Spirituality, 2007)
Keywords: 👤 norbert of xanten

Norbert von Xanten und seine ersten Stifte: Beobachtungen zur rechtlichen Stellung und inneren Struktur - Felten, Franz J. (Oberzell. Vom Prämonstratenserstift (bis 1803) zum Mutterhaus der Kongregation der Dienerinnen, 2006)
Keywords: 👤 norbert of xanten

Een pastoraal offensief in Antwerpen: Norbertus, de volgelingen van Tanchelm, en de stichting van het Sint-Michielsklooster in 1124 - Moolenbroek, Jaap van (Wonderen voor alledag: Elf opstellen over godsdienst en samenleving in de Middeleeuwen door Jaap van Moolenbroek opnieuw uitgegeven bij zijn afscheid van de Vrije Universiteit, 2006)
Keywords: antwerp; 👤 norbert of xanten

Zwischen Berufung und Amt: Norbert von Xanten und seinesgleichen im ersten Viertel des 12. Jahrhunderts - Felten, Franz J. (Charisma und religiöse Gemeinschaften im Mittelalter: Akten des 3. Internationalen Kongresses des "Italienisch-deutschen Zentrums für Vergleichende Ordensgeschichte" in Verbindung mit Projekt C "Institutionelle Strukturen religiöser Orden im Mittelalter" und Projekt W "Stadtkultur und Klosterkultur in der mittelalterlichen Lombardei. Institutionelle Wechselwirkung zweier politischer und sozialer Felder" des Sonderforschungsbereichs 537 "Institutionalität und Geschichtlichkeit" (Dresden, 10.-12. Juni 2004), 2005)
Keywords: 👤 norbert of xanten

Vie de saint Norbert fondateur des prémontrés - Wuillème, Jean (Amalthée, 2005)
Keywords: 👤 norbert of xanten

Norbert von Xanten und der Prämonstratenser-Orden - Horstkötter, Ludger (Netzwerk des Glaubens: Prämonstratenser in Mitteleuropa ; eine Ausstellung des Dommuseums Brandenburg, 2003)
Keywords: 👤 norbert of xanten; 📚 premonstratensian (general)

Augustinusregel, professio canonica und Prämonstratenser im 12. Jahrhundert. Das Beispiel der Norbert-Viten, Philipps von Harvengt und Anselms von Havelberg - Bomm, Werner (Regula Sancti Augustini. Normative Grundlage differenter Verbände im Mittelalter. Tagung der Akademie der Augustiner-Chorherren von Windesheim und des Sonderforschungsbereichs 537, Projekt C "Institutionelle Strukturen religiöser Orden im Mittelalter" vom 14. bis zum 16. Dezember 2000 in Dresden, 2002)
Keywords: 👤 anselm of havelberg; 👤 norbert of xanten; 👤 philip of harvengt

Norbert von Xanten: Vom Rheinland nach Magdeburg. Ein Europäer des 12. Jahrhunderts im Dienst von Kirche und Staat - Horstkötter, Ludger (Mitteldeutsches Jahrbuch für Kultur und Geschichte, 2000)
Keywords: 👤 norbert of xanten

Norbert von Xanten und die Prämonstratenser in Brandenburg - Arndt, Gerda (Jahresbericht über den Historischen Verein zu Brandenburg, 1999)
Keywords: 🇩🇪 germany (general); 👤 norbert of xanten

Bernhard von Clairvaux, Norbert von Xanten und der lateinische Osten - Hiestand, Rudolf (Vita Religiosa im Mittelalter. Festschrift für Kaspar Elm zum 70. Geburtstag, 1999)
Keywords: 🌐 latin east (general); 👤 norbert of xanten

Nam Norbert deel aan de Rometocht van 1110-1111? - Grauwen, Wilfrid (Analecta Praemonstratensia, 1996)
Keywords: 👤 norbert of xanten

Petite vie de saint Norbert : 1080-1134 - Dauzet, Dominique-Marie (Desclée de Brouwer, 1995)
Keywords: 👤 norbert of xanten

De religieuze vorming van Norbert te Siegburg. Was er een ontmoeting met Rupert van Deutz, 1115-1118? - Grauwen, Wilfrid (Analecta Praemonstratensia, 1995)
Keywords: 👤 norbert of xanten

De religieuze vorming van Norbert te Siegburg: Was er een ontmoeting met Rupert van Deutz, 1115-1118? - Grauwen, Wilfried Marcel (Analecta Praemonstratensia, 1995)
Keywords: 👤 norbert of xanten

Norbert doet afstand van zijn goederen. De stichting van Fürstenberg, aug. - sept. 1118 - Grauwen, Wilfried Marcel (Analecta Praemonstratensia, 1995)
Keywords: 👤 norbert of xanten

Norbert of Xanten: Preaching to the people, converting the clergy - Van Engen, John (Reclaiming Our Norbertine Heritage: Lectures Presented in Honor of the 100th Anniversary of the Norbertine Presence in the Green Bay Diocese, 1995)
Keywords: 👤 norbert of xanten

Bartholomeus van Laon en Norbert op zoek naar een vestigingsplaats, begin 1120 - Grauwen, Wilfried Marcel (Analecta Praemonstratensia, 1994)
Keywords: 👤 norbert of xanten

De handschriften van de Vitae Norberti - Grauwen, Wilfried Marcel (Analecta Praemonstratensia, 1994)
Keywords: 👤 norbert of xanten

Norberto reis naar Laon, Kamerijk en Njvel en de inbezitneming van Prémontré, 1120 - Grauwen, Wilfrid (Analecta Praemonstratensia, 1993)
Keywords: 👤 norbert of xanten

De duivelverhalen en het exorcisme van Norbert te Maastricht, 1122 - Grauwen, Wilfried Marcel (Analecta Praemonstratensia, 1993)
Keywords: 👤 norbert of xanten

Hoe Norbert de H. Schrift navolgde - Grauwen, Wilfried Marcel (Analecta Praemonstratensia, 1993)
Keywords: 👤 norbert of xanten

Norbert et de concilies van Keulen en Fritzlar - Grauwen, Wilfried Marcel (Analecta Praemonstratensia, 1993)
Keywords: 👤 norbert of xanten

Norbert predikt te Antwerpen in 1124 - Grauwen, Wilfried Marcel (Analecta Praemonstratensia, 1993)
Keywords: 👤 norbert of xanten

Norberts reis naar Laon, Kamerijk en Nijvel en de inbezitneming van Prémontré, 1120 - Grauwen, Wilfried Marcel (Analecta Praemonstratensia, 1993)
Keywords: 👤 norbert of xanten

Norbert von Xanten bei Propst Richer im Regularkanonikerstift Klosterrath - Deutz, Helmut (Analecta Praemonstratensia, 1992)
Keywords: 👤 norbert of xanten

Bernard et Norbert: eschatologie et reforme - Goetz, H.W. (Bernard de Clairvaux : histoire, mentalités, spiritualité, 1992)
Keywords: 👤 norbert of xanten

Heeft Norbert in 1113/1114 de bisschopszetel van Kamerijk geweigerd? - Grauwen, Wilfried Marcel (Analecta Praemonstratensia, 1992)
Keywords: 👤 norbert of xanten

Norbert als kapelaan van Frederik I van Keulen, 1112 - Grauwen, Wilfried Marcel (Analecta Praemonstratensia, 1992)
Keywords: 👤 norbert of xanten

Norbert als vredesapostel te Fosses, Moustier, Gembloers en Corroy-le-Château, 1119 - Grauwen, Wilfried Marcel (Analecta Praemonstratensia, 1992)
Keywords: 👤 norbert of xanten

Norbert en de stichting van Cappenberg, 1122 - Grauwen, Wilfried Marcel (Analecta Praemonstratensia, 1992)
Keywords: cappenberg; 👤 norbert of xanten

Norbert op het concilie von Reims in oktober 1119 - Grauwen, Wilfried Marcel (Analecta Praemonstratensia, 1992)
Keywords: 👤 norbert of xanten

Norbert en de reliekenvinding te Keulen, 12/13 oktober - 24 november 1121 - Grauwen, Wilfrid (Analecta Praemonstratensia, 1991)
Keywords: 👤 norbert of xanten

De legende van diaken Nicolaas in de Vita Norberti A - Grauwen, Wilfried Marcel (Analecta Praemonstratensia, 1991)
Keywords: 👤 norbert of xanten

De terugkeer van Hugo en de duiveluitdrijving door Norbert te Nijvel, 1121 - Grauwen, Wilfried Marcel (Analecta Praemonstratensia, 1991)
Keywords: 👤 norbert of xanten

Norbert en de reliekenvinding te Keulen, 12/13 october - 24 november 1121 - Grauwen, Wilfried Marcel (Analecta Praemonstratensia, 1991)
Keywords: 👤 norbert of xanten

Norbert reis naar Saint-Gilles-du Gard, 1118 - Grauwen, Wilfried Marcel (Analecta Praemonstratensia, 1991)
Keywords: 👤 norbert of xanten

Over het ontstaan en de groei van de premonstratenzers: vita Norberti B - Grauwen, Wilfried Marcel (Bibliotheca Analectorum Praemonstratensium, 1991)
Keywords: 👤 norbert of xanten

Paus Calixt II te Laon in november 1119 en het "propositum" van Norbert - Grauwen, Wilfried Marcel (Analecta Praemonstratensia, 1991)
Keywords: 👤 norbert of xanten

Vitalis van Savigny en Norbert als "Wanderprediger" - Grauwen, Wilfried Marcel (Analecta Praemonstratensia, 1991)
Keywords: 👤 norbert of xanten

Norbert von Xanten und die Prämonstratenser - Proházka, Karl Michael (Mönchsväter und Ordensgründer : Männer und Frauen in der Nachfolge Jesu, 1991)
Keywords: 👤 norbert of xanten

Inleiding tot de Vita Norberti B - Grauwen, Wilfried Marcel (Analecta Praemonstratensia, 1990)
Keywords: 👤 norbert of xanten

Norbert en de oudste organisatie van de premonstratenzerorde - Grauwen, Wilfried Marcel (Analecta Praemonstratensia, 1990)
Keywords: 👤 norbert of xanten

Saint Norbert, le pèlerin, et les pèlerinages médiévaux de l’ordre de Prémontré - Ardura, Bernard (Medioevo in cammino: l'Europa dei pellegrini : atti del convegno internazionale di studi, Orta San Giulio, 2-5 settembre 1987, 1989)
Keywords: 👤 norbert of xanten

Nogmaals over Abaelard, Bernard en Norbert - Grauwen, Wilfried Marcel (Analecta Praemonstratensia, 1989)
Keywords: 👤 norbert of xanten

Rupert van Deutz en Norbert van Gennep in de recente literatuur - Grauwen, Wilfried Marcel (Analecta Praemonstratensia, 1989)
Keywords: 👤 norbert of xanten

Der heilige Norbert von Xanten und die Prämonstratenser: die kirchliche Erneuerung im 12. Jh. und in unserer heutigen Zeit - Horstkötter, Ludger (Prämonstratenser-Abtei St. Johann, 1989)
Keywords: 👤 norbert of xanten

De crisissituatie van Norbert begin november 1119 en zijn belangstelling voor psalm - Grauwen, Wilfried Marcel (Analecta Praemonstratensia, 1988)
Keywords: 👤 norbert of xanten

Twee onuitgegeven oorkonden over Norbert van Gennep - Grauwen, Wilfried Marcel (Analecta Praemonstratensia, 1988)
Keywords: 👤 norbert of xanten

Het getuigenis van Abaelard over Norbert van Gennep - Grauwen, Wilfried Marcel (Analecta Praemonstratensia, 1987)
Keywords: 👤 norbert of xanten

Die radikale Christusnachfolge des heiligen Norbert von Xanten als geistige Grundlage für die Reformbewegung der Prämonstratenserordens - Horstkötter, Ludger (Hildegunde von Ahr und Meer. Leben und Werk, 1987)
Keywords: 👤 norbert of xanten

Norbert, Erzbischof von Magdeburg (1126-1134) - Grauwen, Wilfried Marcel; Horstkötter, Ludger (Prämonstratenser-Abtei St. Johann, 1986)
Keywords: 👤 norbert of xanten

Norbert von Xanten: Adliger, Ordensstifter, Kirchenfürst - Elm, Kaspar (Wienand, 1984)
Keywords: 👤 norbert of xanten

Die Quellen zur Geschichte Norberts von Xanten - Grauwen, Wilfried Marcel (Norbert von Xanten. Adliger, Ordensstifter, Kirchenfürst, 1984)
Keywords: 👤 norbert of xanten

Een fragment van de Vita Norberti A te Hamburg - Grauwen, Wilfried Marcel (Analecta Praemonstratensia, 1984)
Keywords: 👤 norbert of xanten

Het leven van heer Norbert, aartsbisschop von Maagdenburg. Vita Norberti A. - Grauwen, Wilfried Marcel (Bibliotheca analectorum Praemonstratensium, 1984)
Keywords: 👤 norbert of xanten

Inleiding op de Vita A van de H. Norbertus - Grauwen, Wilfried Marcel (Analecta Praemonstratensia, 1984)
Keywords: 👤 norbert of xanten

Wer war Norbert von Xanten? - Horstkötter, Ludger (Geraser Hefte, 1984)
Keywords: 👤 norbert of xanten

De bronnen voor de geschiedenis van Norbert, stichter van Premontre - Grauwen, Wilfrid M. (Analecta Praemonstratensia, 1983)
Keywords: 👤 norbert of xanten

Guibert van Nogent en Norbert van Gennep - Grauwen, Wilfried Marcel (Analecta Praemonstratensia, 1983)
Keywords: 👤 norbert of xanten

Norbert de Xanten - Calmels, Norbert (Pastorelly, 1981)
Keywords: 👤 norbert of xanten

Kritische Gedanken von Prof. Dr. Kaspar Elm über Charakter und Persönlichkeit des hl. Norbert - Horstkötter, Ludger (Analecta Praemonstratensia, 1981)
Keywords: 👤 norbert of xanten

On the date of John Capgrave's Life of St. Norbert - Lucas, Peter J. (The Library: The Transactions of the Bibliographical Society, 1981)
Keywords: 👤 john capgrave; 👤 norbert of xanten

Norbert et l'origine des Prémontrés - Petit, François (Éditions du CERF, 1981)
Keywords: 👤 norbert of xanten; 📚 premonstratensian (general)

Recente studies over de Vita metrica Norberti door Capgrave (1393-1464) - Grauwen, Wilfried Marcel (Analecta Praemonstratensia, 1979)
Keywords: 👤 john capgrave; 👤 norbert of xanten

Een brief om inlichtingen voor de biografie van Norbertus door Ch.-L. Hugo - Grauwen, Wilfried Marcel (Analecta Praemonstratensia, 1978)
Keywords: 👤 norbert of xanten

Norbertus aartsbisschop van Maagdenburg (1126-1134) - Grauwen, Wilfried Marcel (Verhandelingen van de Koninklijke Academie voor Wetenschappen, Letteren en Schone Kunsten van België, Klasse der Letteren, 1978)
Keywords: 👤 norbert of xanten

The life of St. Norbert by John Capgrave, O.E.S.A.: 1393 - 1464 - Capgrave, John (Studies and texts, 1977)
Keywords: 👤 john capgrave; 👤 norbert of xanten

De geschiedenis van Gennep en de afstamming van Norbertus - Grauwen, Wilfried Marcel (Analecta Praemonstratensia, 1977)
Keywords: 👤 norbert of xanten

De Norbertusbiografie in de geschiedenis van het aartsbisdom Maagdenburg - Grauwen, Wilfried Marcel (Analecta Praemonstratensia, 1977)
Keywords: magdeburg; 👤 norbert of xanten

Lijst van oorkonden waarin Norbertus wordt genoemd - Grauwen, Wilfried Marcel (Analecta Praemonstratensia, 1975)
Keywords: 👤 norbert of xanten

Norbert et les débuts de l'abbaye de Floreffe - Grauwen, Wilfried Marcel (Analecta Praemonstratensia, 1975)
Keywords: floreffe; 👤 norbert of xanten

Norbert van Gennep en de "Orde canonicus". Evangelisch leven tussen restauratie en vernieuwing - Dijck, L. van C. (Ons geestelijk erf, 1974)
Keywords: 👤 norbert of xanten; 📚 premonstratensian (general)

John Capgrave's first English composition, "The Life of St. Norbert" - Fredeman, Jane Cowan (Bulletin of the John Rylands Library, 1974)
Keywords: 👤 john capgrave; 👤 norbert of xanten

Was Norbertus tevens kanunnik van Sint-Servaas te Maastricht? - Grauwen, Wilfried Marcel (Analecta Praemonstratensia, 1974)
Keywords: 👤 norbert of xanten

Herman van Doornik en Norbertus - Grauwen, Wilfried Marcel (Analecta Praemonstratensia, 1972)
Keywords: 👤 norbert of xanten

Het Polenprivilege van Norbertus, 4 juni 1133 - Grauwen, Wilfried Marcel (Analecta Praemonstratensia, 1972)
Keywords: 👤 norbert of xanten

Norbertus en de brand te Kamerijk in 1123 - Grauwen, Wilfried Marcel (Analecta Praemonstratensia, 1972)
Keywords: 👤 norbert of xanten

Capgrave's Life of St. Norbert: direction, dialect and spelling - Smetana, Cyril Lawrence; Colledge, Edmund (Mediaeval Studies, 1972)
Keywords: 👤 john capgrave; 👤 norbert of xanten

De "Vitae" van Norbertus - Grauwen, Wilfried Marcel (Analecta Praemonstratensia, 1966)
Keywords: 👤 norbert of xanten

Norbert en Gennep - Grauwen, Wilfried Marcel (Analecta Praemonstratensia, 1966)
Keywords: 👤 norbert of xanten

Saint Norbert et les institutions de l'Eglise carolingienne - Petit, François (Analecta Praemonstratensia, 1966)
Keywords: 👤 norbert of xanten

Note sulle "Vitae" Di Norberto di Xanten - Fumagalli, Vito (Aevum, 1965)
Keywords: 👤 norbert of xanten

S. Norbertus - Grauwen, Wilfried Marcel (Analecta Praemonstratensia, 1965)
Keywords: 👤 norbert of xanten

Pourquoi saint Norbert a choisi Prémontré - Petit, François (Analecta Praemonstratensia, 1964)
Keywords: prémontré; 👤 norbert of xanten

Norbert von Magdeburg und Gerhoch von Reichersberg - Klebel, F. W. (Analecta Praemonstratensia, 1962)
Keywords: 👤 norbert of xanten

L'ordre de Prémontré de saint Norbert à Anselme de Havelberg - Petit, François (La vita comune del clero nei secoli XI e XII, 1962)
Keywords: 👤 anselm of havelberg; 👤 norbert of xanten

L'épisode de la conversion de S. Norbert et la tradition hagiographique du "Vita Norberti" - Lefèvre, Placide (Revue d'histoire ecclésiastique, 1961)
Keywords: 👤 norbert of xanten

Comment nous connaissons saint Norbert - Petit, François (Analecta Praemonstratensia, 1960)
Keywords: 👤 norbert of xanten

Saint Norbert, un Européen - Romain, Willy-Paul (E. Vitte, 1960)
Keywords: 👤 norbert of xanten

Le problème de l'ambivalence de la Vita Norberti: Chronique - Lefèvre, Placide (Revue d'histoire ecclésiastique, 1959)
Keywords: 👤 norbert of xanten

Zur Literatur uber den heiligen Norbert - Mannl, Oswald-Louis (Analecta Praemonstratensia, 1959)
Keywords: 👤 norbert of xanten

La spiritualità di S. Norberto (II) - Santa, Dino Suor (Analecta Praemonstratensia, 1959)
Keywords: 👤 norbert of xanten

De oudste levensbeschrijving van Sint Norbert - Klesser, O. (Analecta Praemonstratensia, 1958)
Keywords: 👤 norbert of xanten

La spiritualità di S. Norberto (I) - Santa, Dino Suor (Analecta Praemonstratensia, 1958)
Keywords: 👤 norbert of xanten

Saint Norbert, soldat de lumière, fondateur de l'ordre de Prémontré, archevêque de Magdebourg - Almira de Saint Clet, José (Le rameau, 1955)
Keywords: 👤 norbert of xanten

Nochmals St. Norbert und die Camera Castitatis in Xanten. - Engelskirchen, Heinrich (Analecta Praemonstratensia, 1955)
Keywords: 👤 norbert of xanten

Zur Bekehrung des hl. Norbert. - Engelskirchen, Heinrich (Analecta Praemonstratensia, 1955)
Keywords: 👤 norbert of xanten

St. Norbert und die Casa castitatis in Xanten - Engelskirchen, Heinrich (Analecta Praemonstratensia, 1954)
Keywords: 👤 norbert of xanten

Vida de São Norberto : fundador da Ordem Premonstratense, Arcebispo de Magdeburgo - Adriaansen, Guilherme (Editora Vozes, 1953)
Keywords: 👤 norbert of xanten

Prince du Nord; vie de saint Norbert, fondateur des prémontrés, archevêque de Magdebourg - André, Joseph (Abbaye Saint-Michel de Frigolet, 1953)
Keywords: 👤 norbert of xanten

Ein Xantener Dechant über den hl. Norbert - Engelskirchen, Heinrich (Analecta Praemonstratensia, 1951)
Keywords: 👤 norbert of xanten; 📚 premonstratensian (general)

Xanten und die Kreuzzugsbewegung. Aus den Togen des Hl. Norbert - Engelskirchen, Heinrich (Analecta Praemonstratensia, 1950)
Keywords: 👤 norbert of xanten

Nova Norbertina I, II, III: Neue Forschungsergebnisse über Norbert von Xanten - Engelskirchen, Heinrich (Analecta Praemonstratensia, 1946)
Keywords: 👤 norbert of xanten

Saint-Norbert et le culte eucharistique - Lefèvre, Placide (Studia eucharistica DCCI anni a condito festo Sanctissimi Corporis Christi (1246-1946), 1946)
Keywords: 👤 norbert of xanten

Une compétition de sculpteurs pour la statue de St Norbert à Rome - Lamy, Hugues (Revue belge d'archéologie et d'histoire de l'art, 1941)
Keywords: 👤 norbert of xanten

L'érection de la statue de saint Norbert dans la basilique de Saint-Pierre à Rome - Lamy, Hugues (Analecta Praemonstratensia, 1940)
Keywords: 👤 norbert of xanten

Norbert von Xanten: ein heiliger deutscher Staatsmann - Ulmer-Stichel, Dörthe (Verlag der Buchgemeinde Bonn, 1940)
Keywords: 👤 norbert of xanten

Les fêtes jubilaires de Saint Norbert à Xanten - Valvekens, Johannes B. (Analecta Praemonstratensia, 1935)
Keywords: 👤 norbert of xanten

Emlékkönyv Szent Norbert halálának 800 éves jubileumára: Fejezetek a magyar premontreiek 800 éves multjából (A jászó-premontrei kanonokrend gödöllői Konventje, 1934)
Keywords: 🇭🇺 hungary (general); 👤 norbert of xanten; 📚 premonstratensian (general)

Liber memorialis in honorem S. Norberti: 1134-1934 (Averbode Abbey, 1934)
Keywords: 👤 norbert of xanten

Autour de l'oeuvre des hagiographes de saint Norbert - Erens, Ambrosius (Analecta Praemonstratensia, 1934)
Keywords: 👤 norbert of xanten

Norbert van Gennep: een pelgrim op aarde - Schreurs, Jacques (Geert-Groote-Genootschap, 1934)
Keywords: 👤 norbert of xanten

De heilige Norbertus en de strijd tegen het Tanchelmisme te Antwerpen - Philippen, Louis J. M. (Bijdragen tot de geschiedenis, 1933)
Keywords: 👤 norbert of xanten

Vita S. P. Norberti in archivo abbatiae Grimbergensis - Delestré, Jules Daniel (Analecta Praemonstratensia, 1930)
Keywords: grimbergen; 👤 norbert of xanten

Der heilige Norbert: ein Lebensbild nach der Kirchen- und Profangeschichte - Žák, Alfons (Kleine historische Monographien, 1930)
Keywords: 👤 norbert of xanten

Strahov : k třístému jubileu sv. Norberta, ochránce země české - Ondrácek, Vilém (nákladem vlastním, 1927)
Keywords: strahov; 👤 norbert of xanten

L'Exhortatio de S. Norbert - Erens, Ambrosius (Analecta Praemonstratensia, 1926)
Keywords: 👤 norbert of xanten

St. Bernhard und St. Norbert und die Freundschaft ihrer Orden - Žák, Alfons (Cistercienser Chronik, 1919)
Keywords: 👤 norbert of xanten; 📚 premonstratensian (general)

History of Saint Norbert, founder of the Norbertine (Premonstratensian) Order, Apostle of the Blessed Sacrament, Archbishop of Magdeburg - Kirkfleet, Cornelius J (B. Herder, 1916)
Keywords: 👤 norbert of xanten

Der hl. Norbert: Stifter des Prämonstratenser-Ordens und Erzbischof von Magdeburg - Wozasek, Bartholomaeus (Eichinger, 1914)
Keywords: 👤 norbert of xanten

Szent Norbert élete - Madelaine, Godefroid; Takács Menyhért (Stephaneum Nyomda, 1905)
Keywords: 👤 norbert of xanten

Der heilige Norbert, Herr von Gennep, Stifter des Prämonstratenserordens und Erzbischof von Magdeburg: ein Lebensbild - Žák, Alfons (Verlag der "St. Norbertus" Buch-und Kunstdruckerei, 1900)
Keywords: 👤 norbert of xanten

Vie de Saint Norbert, archevêque de Magdebourg, fondateur de l'ordre de Prémontré : tableaux historiques du XIIe siècle offerts à la jeunesse - Spilbeeck, Ignace van (Société Belge de librairie, 1898)
Keywords: 👤 norbert of xanten

The life of S. Norbert, founder of the Order of Prémontré, Archbishop of Magdeburg - Geudens, Martin (R. Washbourne, 1886)
Keywords: 👤 norbert of xanten

Histoire de saint Norbert, fondateur de l'ordre de Prémontré et archevêque de Magdebourg : d'après les manuscrits et les documents originaux - Madelaine, Godefroid (Impr. de Desclée, de Brouwer et Cie, 1886)
Keywords: 👤 norbert of xanten

Leben des heiligen Norbert, Erzbischofs von Magdeburg : nebst der Lebensbeschreibung des Grafen Gottfried von Kappenberg und Auszügen aus verwandten Quellen - Hertel, Gustav (Geschichtschreiber der deutschen Vorzeit, 1881)
Keywords: cappenberg; 👤 norbert of xanten

Svatý Norbert, arcibiskup Magdeburský, patriarcha a zakladatel řádu ... - Čermak, Dominik Karel (Cyrillo-Methodějská kněhtiskárna, Nakl. kanonie Strahovské, 1877)
Book digitized by Google from the library of the University of Michigan and uploaded to the Internet Archive by user tpb.
Keywords: 👤 norbert of xanten

Norbert von Prémontré und Magdeburg - Bernheim, Ernst (Historische Zeitschrift, 1876)
Keywords: 👤 norbert of xanten

Histoire de Prémontré, précédé de la Vie de Saint Norbert - Valissant, Armand (Impr. H. Jacob, 1876)
Keywords: prémontré; 👤 norbert of xanten

Vie de Saint Norbert: fondateur de l'ordre des chanoines réguliers de Prémontré - Liguori, Alphonse de (H. Goemaere, 1866)
Keywords: 👤 norbert of xanten

Vie de Saint-Norbert, fondateur de l'ordre de Prémontré - Bernard (Actes de la Société Jurassienne d'émulation, 1857)
Keywords: 👤 norbert of xanten

Historia del gran Padre, y Patriarcha San Norberto: Historia de los varones ilustres del Orden Candido Premonstratense de Canonigos Reglares del gran Padre y Doctor de la Iglesia San Agustin - Abad Illana, Manuel (1760)
Keywords: 👤 norbert of xanten

Historia del gran Padre, y Patriarcha San Norberto - Abad Illana, Manuel (1755)
Keywords: 👤 norbert of xanten

Vie de St. Norbert, fondateur des Prémontrés - Hugo, Charles Louis (Chez André Chevalier, 1704)
Keywords: 👤 norbert of xanten

S. Norberti archiepiscopi magdeburgensis candidissimae religionis canonicorum praemonstratensium fundatoris ac patriarchae sermo ad eodem praemonstratenses filios quondam dictus et scriptus - Hirnhaim von Elsenberg, Hieronymus (Jiří Černoch, 1676)
Keywords: 👤 norbert of xanten

La Vie du bienheureux saint Norbert, fondateur de l'ordre de Prémonstré ... contenant l'origine, progrès et avancement de l'ordre de Prémonstré, et autres choses remarquables, notamment l'invention du corps dudit S. Norbert, et les magnificences faites en sa translation à Prague, en cette année 1627. Ensemble une petite chronique sur la vie de saint Norbert, et un discours sur l'excellence de l'habit blanc des religieux de l'ordre de Prémonstré - Du Pré, Maurice (H. Blageart, 1627)
Keywords: 👤 norbert of xanten